2014
DOI: 10.1186/1742-2094-11-72
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 promotes the interleukin-4-induced alternative activation in BV-2 microglial cells

Abstract: BackgroundMicroglia play key roles in innate immunity, homeostasis, and neurotropic support in the central nervous system. Similar to macrophages, microglia adopt two different activation phenotypes, the classical and alternative activation. Resolvin D1 (RvD1) is considered to display potent anti-inflammatory and pro-resolving actions in inflammatory models. In this present study, we investigate the effect of RvD1 on IL-4-induced alternative activation in murine BV-2 microglial cells.MethodsBV-2 cells were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…Binding separation of the protein DNA complexes from unbound DNA by electrophoresis was performed as previously described in detail (26). Nuclear protein after 1 h of S100A8/A9 treatment and a 200-fold molar excess of unlabeled consensus sequence were used as the specific competitor in the control lane.…”
Section: Methodsmentioning
confidence: 99%
“…Binding separation of the protein DNA complexes from unbound DNA by electrophoresis was performed as previously described in detail (26). Nuclear protein after 1 h of S100A8/A9 treatment and a 200-fold molar excess of unlabeled consensus sequence were used as the specific competitor in the control lane.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have reported that RvD1 promotes alternative activation of macrophages (the M2 phenotype) 11,50 and that the M2 macrophages appear to mitigate inflammation and promote the resolution of inflammation in acute models and cell culture systems. 11,51 However, some evidence suggests that in chronic diseases, M2 macrophages may promote tissue remodeling and repair, leading to fibrosis. 38 In our model of long-term smoke exposure with AT-RvD1 treatment, we did not find evidence of preferential M1 or M2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 2 SPMs 15-epi-LXA 4 and RvD1 were employed to determine their activity in modulating autophagy in macrophages. First, we incubated murine peritoneal macrophages with different concentrations of these pro-resolving lipids at concentration ranges at which they have previously been shown to activate significant pro-resolving actions 12,14,37 to determine the potential effects on MAP1LC3 processing (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%